Comparison of the oncological, perioperative and functional outcomes of partial nephrectomy versus radical nephrectomy for clinical T1b renal cell carcinoma: A systematic review and meta-analysis of retrospective studies - Yucong Zhang; Gongwei Long; Haojie Shang; Beichen Ding; Guoliang Sun; Wei Ouyang; Man Liu; Yuan Chen; Heng Li; Hua Xu; Zhangqun Ye (Asian Journal of Urology, 2021)
Objective: To conduct a meta-analysis assessing the perioperative, functional and oncological outcomes of partial nephrectomy (PN) and radical nephrectomy (RN) for T1b tumours. The primary endpoints were the oncological outcomes. The secondary endpoints were the perioperative and functional outcomes. Methods: A systematic literature review was performed by searching multiple databases through February 2019 to identify eligible comparative studies according to the Preferred Reporting Items for Systematic Review and Meta-analysis statement. Identified reports were assessed according to the Newcastle-Ottawa Scale for nonrandomized controlled trials. Results: Overall, 13 retrospective cohort studies were included in the analysis. Patients undergoing PN were younger (weighted mean difference [WMD] −3.49 years, 95% confidence interval [CI] −5.16 to −1.82; p<0.0001) and had smaller masses (WMD −0.45 cm, 95% CI −0.59 to −0.31; p<0.0001). There were no differences in the oncological outcome, which was demonstrated by progression-free survival (hazard ratio [HR] 0.70; p=0.22), cancer-specific mortality (HR 0.91; p=0.57) and all-cause mortality (HR 1.01; p=0.96). The two procedures were similar in estimated blood loss (WMD −16.47 mL; p=0.53) and postoperative complications (risk ratio [RR] 1.32; p=0.10), and PN provided better renal function preservation and was related to a lower likelihood of chronic kidney disease onset (RR 0.38; p=0.006). Conclusion: PN is an effective treatment for T1b tumours because it offers similar surgical morbidity, equivalent cancer control, and better renal preservation compared to RN.